The state within a state : the KGB and its hold on Russia--past, present, and future - Albats, Yevgenia (Farrar Straus Giroux, 2006)
In this riveting and immensely readable investigation, Yevgenia Albats, one of Russia's leading journalists, explodes the myth that the KGB died - or even faded away - when the Soviet empire broke apart. Albats makes the shocking claim that the same group which proudly traces its lineage to Stalin's brutally repressive secret police actually engineered the policy of perestroika, subtly and effectively controlling the overhaul of Soviet society in order to reposition itself at the top. Drawing on a wealth of unpublished documents from the KGB's secret files and on rare interviews with victims as well as interrogators, Albats chronicles the KGB's evolution into the world's largest secret police force. She shows how it infiltrated every structure of civil society and every aspect of daily life; how it choreographed the "unsuccessful" coup of August 1991; and how, despite its official dissolution in the new democratic Russia, the KGB is stronger than ever, having transformed itself from an instrument of state power to a state power in its own right.